2022
DOI: 10.1093/eurpub/ckac135
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination barriers and drivers in Romania: a focused ethnographic study

Abstract: Background In 2016–18, a large measles outbreak occurred in Romania identified by pockets of sub-optimally vaccinated population groups in the country. The aim of the current study was to gain insight into barriers and drivers from the experience of measles vaccination from the perspectives of caregivers and their providers. Methods Data were collected by non-participant observation of vaccination consultations and individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…During the last measles outbreak of 2016–2020, these groups were disproportionately affected by the disease, which clearly indicated inequities in immunization [ 15 ]. A recently published ethnographic study on the barriers and drivers towards vaccination in Romania identified disparities in clinics with low and high vaccine coverage rates (in terms of contraindication assessment, type of information provided to the child’s caregiver related to adverse events, openness to questions, appointment scheduling and correctitude of administration techniques) and defined interventions to increase the training of healthcare providers and to improve the services for the vulnerable and disadvantaged population [ 19 ]. A mid-term term solution could be the establishment of community centers, delivering integrated health care and prevention services, including vaccination and vaccine-related education.…”
Section: Discussionmentioning
confidence: 99%
“…During the last measles outbreak of 2016–2020, these groups were disproportionately affected by the disease, which clearly indicated inequities in immunization [ 15 ]. A recently published ethnographic study on the barriers and drivers towards vaccination in Romania identified disparities in clinics with low and high vaccine coverage rates (in terms of contraindication assessment, type of information provided to the child’s caregiver related to adverse events, openness to questions, appointment scheduling and correctitude of administration techniques) and defined interventions to increase the training of healthcare providers and to improve the services for the vulnerable and disadvantaged population [ 19 ]. A mid-term term solution could be the establishment of community centers, delivering integrated health care and prevention services, including vaccination and vaccine-related education.…”
Section: Discussionmentioning
confidence: 99%
“…Данный метод был апробирован в ряде стран и доказал свою эффективность с целью выявления факторов, препятствующих или способствующих вакцинации [24][25][26][27][28].…”
Section: Discussionunclassified
“…Данный подход разработан на основании комплексной модели COM-B и адаптирован к контексту изучения поведенческих факторов в отношении вакцинации против COVID-19 в ряде документов ВОЗ 4 , а затем применительно к вакцинации в целом. Данный инструмент был апробирован в ряде стран: Босния и Герцеговина, Северная Македония и Румыния [24][25][26][27][28].…”
Section: материал и методыunclassified
“…Further, there are frequent trips back and forth between France and Romania, where measles remains endemic, with 17 533 cases and 64 deaths between January 2016 and July 2019 in Romania 8 . In 2018, measles‐containing vaccine (MCV)‐2 coverage was 81%, but several studies have shown that vaccination coverage was lower among disadvantaged communities in Romania, such as the Roma 15,16 . Factors contributing to low vaccination coverage among Roma in both Romania and France include inadequate implementation of public health measures and reluctance to be vaccinated, ranging from disadvantaged communities viewing prevention as less important to strong reluctance exacerbated by misinformation or disinformation, and religious impregnations.…”
Section: Discussionmentioning
confidence: 99%
“…Factors contributing to low vaccination coverage among Roma in both Romania and France include inadequate implementation of public health measures and reluctance to be vaccinated, ranging from disadvantaged communities viewing prevention as less important to strong reluctance exacerbated by misinformation or disinformation, and religious impregnations. Barriers are also related to caregivers’ shortcomings in following recommended practices 16,17 . Proof of vaccination is often missing if the vaccination took place outside Loire‐Atlantique, as electronic vaccination records are not widely used in France, and paper records are often lost.…”
Section: Discussionmentioning
confidence: 99%